2018
DOI: 10.1017/s0033291718001095
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood alcohol outlet density and genetic influences on alcohol use: evidence for gene–environment interaction

Abstract: The results suggest that living in a neighborhood with many alcohol outlets may be especially high-risk for those individuals who are genetically predisposed to frequently drink.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 57 publications
(66 reference statements)
1
11
0
Order By: Relevance
“…Similar to prior studies with younger adults, ( Slutske et al, 2019a , Slutske et al, 2019b ) in the full national sample, the effect of first-degree relatives and high FH density on high-risk drinking strengthened as alcohol availability increased. Post hoc analyses showed this did not vary systematically by age, although our results suggest there may be different combinations of risk factors that are salient for certain population subgroups.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Similar to prior studies with younger adults, ( Slutske et al, 2019a , Slutske et al, 2019b ) in the full national sample, the effect of first-degree relatives and high FH density on high-risk drinking strengthened as alcohol availability increased. Post hoc analyses showed this did not vary systematically by age, although our results suggest there may be different combinations of risk factors that are salient for certain population subgroups.…”
Section: Discussionsupporting
confidence: 76%
“…( Livingston et al, 2007 ) Kendler et al ( Kendler et al, 2011 ) found more pronounced genetic effects on alcohol consumption when access to alcohol was high, and this finding replicates at the area level. Specifically, one study of young adults found heritability of frequent drinking was stronger in areas with higher levels of alcohol availability than in areas without alcohol outlets, ( Slutske et al, 2019 ) suggesting a lack of social control strengthens expression of genetic predispositions to heavy alcohol use.…”
Section: Introductionmentioning
confidence: 99%
“…For example, an individual who is genetically at risk for alcohol use disorder (AUD) will never develop an AUD if he/she is not exposed to alcohol. The importance of genetic influences on substance use outcomes is known to vary as a function of several environmental factors, including parental monitoring, peer deviance, neighborhood characteristics, and romantic relationship status (Barr et al, 2019; Dick et al, 2007; Harden, Hill, Turkheimer, & Emery, 2008; Rose, Dick, Viken, & Kaprio, 2001; Slutske, Deutsch, & Piasecki, 2019).…”
mentioning
confidence: 99%
“…We also expected that neighborhood-level stressors would interact with genetic risk in association with externalizing behaviors, but this dual hazards hypothesis was not supported. Earlier twin and family studies have shown gene–environment interplay, including interactions of genetic risk with neighborhood disadvantage and other neighborhood exposures in relation to both adolescent externalizing behaviors [35,36] and alcohol use [37,38]. There also is evidence for gene-by-environment relationships from molecular genetic studies for externalizing behaviors [32] and alcohol use [16].…”
Section: Discussionmentioning
confidence: 99%
“…Twin and family research show environmental influences on externalizing behaviors are stronger among those living in more disadvantaged neighborhoods [35,36], suggesting high-risk environments play a strong role in the expression of the phenotype. Evidence from studies of high residential mobility [37] and increased alcohol outlet density [38] similarly point to the influence of neighborhood context in enhancing genetic effects for adolescent and young adult alcohol use.…”
Section: Introductionmentioning
confidence: 99%